Pedagogical Principles of Using Naqshbandiya Doctrine in Educating the Young Generation (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
To study the role of Bahovuddin Naqshband's scientific heritage in the development of contemporary pedagogy, the use of Bahovuddin Naqshband's educational and moral views, rich heritage in the process of teaching students.